Perancangan Sistem Informasi Pengingat Jadwal Kegiatan Harian Berbasis Mobile Untuk Meningkatkan Manajemen Waktu - Alda, Muhamad; Manik, Aprilia Lavigne; Agustina, Sofia; Marpaung, Lisa Fauziah; Adella, Anggun (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The rapid development of information technology provides convenience in various aspects of life, but it also creates challenges in time management due to high levels of distraction. Each individual has different daily activities, which require effective schedule management to ensure productivity. This study aims to design a mobile-based daily activity reminder information system to improve users’ time management. The research method used is qualitative, with data collection techniques including literature study and interviews. The system development method applied is the prototype method, which consists of communication, quick plan, modelling, construction, and deployment stages. The results of this study are the design and prototype of a daily activity reminder application equipped with scheduling features and reminder notifications before, during, and after activities. This application is expected to assist users in managing daily activities more systematically and improving awareness of time management.